The effect of heavy resistance exercise on repeated sprint performance in youth athletes - Low, D.; Harsley, P.; Shaw, M.; Peart, D. (Journal of Sports Sciences, 2015)
This investigation assessed whether prior heavy resistance exercise would improve the repeated sprint performance of 16 trained youth soccer players (Age 17.05 ± 0.65 years; height 182.6 ± 8.9 cm; body mass 77.8 ± 8.2 kg). In session 1, individual 1 repetition max was measured utilising a squat movement. In sessions 2 and 3, participants performed a running-based repeated anaerobic sprint test with and without prior heavy resistance exercise of 91% of their 1 repetition max. Times were recorded for each of the 6 sprints performed in the repeated sprint test and summed to provide total time. T-tests compared the two exercise conditions via differences in corresponding sprint times and total time. Analysis revealed significantly reduced total time with use of heavy resistance exercise (33.48 (±1.27) vs. 33.59 (±1.27); P = 0.01). Sprints 1 (P = 0.05) and 2 (P = 0.02) were also faster in the heavy resistance exercise condition (5.09 (±0.16) vs. 5.11 (±0.16) and 5.36 (±0.24) vs. 5.45 (±0.26) seconds respectively) although no other differences were shown. Findings demonstrate improved sprint times of trained adolescent soccer players after heavy resistance exercise although benefits appear not as sustained as in adult participants.